Fostering Scientific Communication in Elementary Science Learning Through Game-Based Toulmin Argumentation - Putra, M. Jaya Adi; Mailinda, Desi Yusnita (Jurnal Pendidikan MIPA, 2025)
This study aims to investigate the potential of science-themed educational games in improving the scientific communication skills of elementary school students. The main focus lies in examining the development of students' ability to express ideas, build arguments, and use scientific vocabulary in an authentic and engaging learning context. This study used a naturalistic qualitative approach with a case study design. Data were collected through participatory observation, audio-video recordings of classroom activities, and documentation of students’ work in grade V of a public elementary school. Thematic analysis was used to interpret the data, supported by the application of the Toulmin Argumentation Pattern (TAP) framework. This framework facilitates the identification of key argument components, including claims, data, guarantees, qualifications, and rebuttals. The findings show that the game "Science Monopoly" effectively stimulates various forms of scientific communication in a natural way. Students presented claims and backed them up with data relevant to the science topic being discussed. However, this study also reveals significant limitations in the development of justification and the use of capital markers, which appear to be less prominent in student discourse. The word cloud analysis further highlights that the scientific vocabulary used by students is primarily concerned with themes such as the water cycle, the Earth's rotation, and the solar system. These results suggest that integrating science content into educational game formats can significantly increase student engagement and deepen their conceptual understanding of scientific phenomena. Based on these findings, the study recommends integrating science literacy-oriented educational games into formal instructional settings. Such integration should be supported by the use of multimodal representations and the structured scaffolding of educators to develop students' scientific communication skills further. This research contributes to the advancement of participatory and meaningful science learning strategies that encourage critical thinking from an early age.    Keywords: verbal interaction, educational games, science literacy, scientific communication, Toulmin Argumentation Pattern, basic education.